The Littles to the rescue - Peterson, John Lawrence, 1924-; Clark, Reberta Carter (New York : Scholastic, 1968)
A family of tiny people experiences a crisis when a baby is born during a snowstorm.
"A Little Apple paperback."
Reading level: 3.0.
500
Accelerated Reader AR
Keywords: Little family (Fictitious character) -- Juvenile fiction; Birth -- Juvenile fiction; Fantasy fiction